The effect of repeated sprint ability on physiological and physical profiles of young basketball players. [El efecto de esprines repetidos en los perfiles fisiológicos y físicos de jóvenes jugadores de baloncesto]. - Rūtenis Paulauskas; Nerijus Masiulis; David Cárdenas; Bruno Figueira; Nuno Mateus; Jaime Sampaio (Ramón Cantó Alcaraz, 2018)
The purpose of this study was to describe the dynamics of a repeated sprint ability (RSA) cycling protocol in young elite basketball players. Twenty-two elite male basketball players (aged 18.3±0.6 years; training years 9.1±1.3 years) performed 3 bouts of a repeated sprint ability (RSA) protocols, consisting of 5 x 6-s cycling sprints with a 24-s rest interval between sprints. The work decrement during the first trial was high (14.1±4.8%) and after 5-minute rest did not change significantly. The total work decreased by 5.5% in the second work interval and by 2.9% in the third interval. During the 5-minute passive rest, young basketball players' peak power recovered about 90% of the initial levels. It is suggested that rest intervals are sufficient to continue the game with adequate performance potential. A reduction in work decrement, while maintaining the capacity of all sprints, is needed to achieve a higher repeated sprint ability. Resumen El propósito de este estudio fue describir la dinámica de un protocolo de esprines repetidos en jóvenes jugadores de baloncesto. Veintidós jugadores de baloncesto masculino (con edades comprendidas entre 18,3 ± 0,6 años, años de entrenamiento de 9,1 ± 1,3 años) realizaron 3 series de un protocolo de esprín repetido, consistiendo en 5 esprines en cicloergometro de 6-s con de descanso de 24-s entre esprints. La disminución del trabajo durante la primera serie fue alta (14.1 ± 4.8%) y después de 5 minutos de descanso no cambió significativamente. El trabajo total disminuyó en un 5.5% en la segunda serie y en un 2.9% en la tercera. Durante el descanso pasivo de 5 minutos, la potencia máxima de los jóvenes jugadores de baloncesto recuperó aproximadamente hasta un 90% de los niveles iniciales. Se sugiere que los intervalos de descanso sean suficientes para continuar el juego con un potencial de rendimiento adecuado. Se necesita una reducción en el decremento del trabajo, mientras se mantiene la capacidad de todos los esprines, para optimizar esta capacidad de rendimiento tan importante en baloncesto.